Factor XI Assembly and Activation on Human Umbilical Vein Endothelial Cells in Culture - Shariat-Madar, Zia; Mahdi, Fakhri; Schmaier, Alvin (Thrombosis and Haemostasis, 2001)
Biotin-FXI optimally bound to HUVEC in the presence of 40 nM high molecular weight kininogen (HK) and ≥ ≥7 μM Zn2+. There was little specific FXI binding in the absence of added HK and at concentrations of Zn2+ <15 μM. FXI and prekallikrein, but not prothrombin, blocked biotin-FXI binding to HUVEC in the presence of HK with an IC50 of 18 nM and 180 nM, respectively. Monoclonal antibody HKL16 and peptide SDD31 also inhibited biotin-XI binding in the presence of HK with an IC50 of 4.7 nM and 50 μM, respectively. Alternatively, peptide T249-F260 of FXI’s apple domain 3 and heparin monosulfate were weak inhibitors of FXI binding to HUVEC. FXI bound to HUVEC with an apparent Kd of 6.9 ± 3.0 nM and Bmax of 13 ± 2.6106 sites/cell. FXI bound to HK on HUVEC, but not prothrombin, became converted to FXIa. FXI activation on HUVEC resulted from tissue culture media bovine factor XIIa. HUVEC grown in human factor XII-deficient serum did not support FXI activation. FXI binding to HUVEC in culture was mostly mediated by HK and FXI activation on HUVEC is dependent on cell-associated factor XIIa.
Keywords: Factor XI; high molecular weight kininogen; factor XII; prekallikrein; prothrombin